2017
DOI: 10.1016/j.jcat.2017.02.022
|View full text |Cite|
|
Sign up to set email alerts
|

A mechanistic basis for the effect of aluminum content on ethene selectivity in methanol-to-hydrocarbons conversion on HZSM-5

Abstract: Increasing crystallize size or aluminum content in MFI-type zeolites independently enhances the propagation of the aromatics-based methylation/dealkylation cycle relative to that of the olefinsbased methylation/cracking cycle in methanol-to-hydrocarbons (MTH) conversion and consequentially results in higher ethene selectivity. We report that ethene selectivity increases monotonically with increasing aluminum content for ZSM-5 samples with nearly identical crystallite size as a follow-up to our recent report de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 45 publications
1
63
0
Order By: Relevance
“…An increase of Al content enhances the chance of reactant molecules to interact with each other, thus increasing the chance to form aromatics and ethylenethe product of the aromatic cycle. 97 The observed trends also account for the improved selectivity to propylene for post-synthetically modified catalysts with different elements as well demetalated zeolites. It has been extensively shown that phosphatation and incorporation of alkaline-earth metals lead to a significant reduction of Brønsted acidity and its effect can be regarded as an increase in the Si/Al ratio.…”
Section: Impact Of Acidity On Stability and Product Selectivitymentioning
confidence: 87%
“…An increase of Al content enhances the chance of reactant molecules to interact with each other, thus increasing the chance to form aromatics and ethylenethe product of the aromatic cycle. 97 The observed trends also account for the improved selectivity to propylene for post-synthetically modified catalysts with different elements as well demetalated zeolites. It has been extensively shown that phosphatation and incorporation of alkaline-earth metals lead to a significant reduction of Brønsted acidity and its effect can be regarded as an increase in the Si/Al ratio.…”
Section: Impact Of Acidity On Stability and Product Selectivitymentioning
confidence: 87%
“…The group of Bhan [19,20] has proposed different selectivity ratios in order to quiantify the importance of each cycle, e.g., the ethylene/isobutane ratio is representative of the arene/olefin cycle ratio [19]. Thus, Figure 5 displays the values of ethylene/isobutane ratio at different temperatures for time on stream values of 0 and 18 h. As observed, the arene cycle dominates at lower temperatures and longer time on stream values.…”
Section: Coke Naturementioning
confidence: 98%
“…In this type of zeolites and zeotypes, DTO mechanism is assumed to occur through the "dual cycle mechanism" (similar to MTO), with olefins and arenes (alkyl-benzenes) being the intermediates in the oligomerization-cracking and olefin/aromatic methylation-dealkylation routes [19]. The pore topology of HZSM-5 zeolite makes the arene cycle particularly dominating for highly acid catalysts [20]. Regarding the arene cycle, the species involved decrease their DTO activity when they are highly methylated or alkylated [21].…”
Section: Introductionmentioning
confidence: 99%
“…The lines of these figures correspond to experiments using different n BAS /Fat TOS = 20 min whereas the points represent variable TOS at n BAS /F = 196.3 μmol BAS h mol CH3 À 1 . Those indexes previously used in the literature [20,23,56,57] enable to study the dual cycle mechanism on the MTH reaction and compare the effect of the conversion or the co-feeding of different species. In this work, we have used the same mechanistic concepts to compare the MTH, DTH and CTH reactions.…”
Section: Fixed-bed Reactor Runsmentioning
confidence: 99%